High-magnetic-permeability nanocrystalline magnetic core and preparation method thereof
By performing multiple steps on the nanocrystalline strip and wrapping it with composite magnetic powder material, a nanocrystalline core with high magnetic permeability is solved, and the problem of difficult balance between the core volume and strength in the existing technology is achieved, and performance improvement and structural stability are achieved Increased sexuality.
Patent Information
- Application Number
- CN202411431466.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-14
AI Technical Summary
In the prior art, the core volume and core strength cannot be effectively balanced, resulting in the performance attenuation of the magnetic core and structural rupture in high-frequency applications.
By winding, heat treatment, impregnating and baking the nanocrystalline strip material, a magnetic core roll is formed, and then the composite magnetic powder material of metal magnetic powder and organic resin is wrapped on the surface of the magnetic core by injection molding to form a nanocrystalline magnet with high magnetic permeability core.
The core strength is improved without increasing volume, which improves high-frequency performance and avoids attenuation and rupture problems of the core during winding.
Smart Images

Figure CN119480325A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic materials, and in particular to a high-permeability nanocrystalline magnetic core and a preparation method thereof. Background Art
[0002] Amorphous nanocrystalline soft magnetic alloys have high magnetic permeability, low coercivity, and excellent high-frequency soft magnetic properties. In recent years, they have received extensive attention and research from academia and the business community. With the rapid development of computer network technology, 5G communications, electric vehicles, photovoltaic new energy, and multimedia technology, electronic devices have been required to be miniaturized, energy-efficient, and high-frequency, which has put forward newer and higher requirements for soft magnetic materials, that is, soft magnetic materials are required to have higher saturation magnetic induction intensity, higher magnetic permeability, lower loss, and good high-frequency performance.
[0003] Since iron-based nanocrystalline alloy soft magnetic materials have the advantages of low loss and high Bs compared with traditional magnetic powder core materials, there is a huge market space for energy storage inductors and common mode inductors for power devices such as new energy vehicles and server power supplies, especially in the field of new energy vehicles and charging piles. At present, traditional nanocrystalline alloy magnetic rings mainly use plastic shells or spray epoxy resin paint to protect the magnetic core. However, both methods have their own defects. For shell protection, a little gap must be left between the magnetic core and the shell, and the shell wall thickness basically needs to reach 1.0mm to facilitate molding and have a certain strength, which leads to an increase in the volume of the magnetic core, and when the device is made, it leads to an increase in copper wire and an increase in the volume of the power supply, etc. Unfavorable factors. Due to the limited strength of the paint, the magnetic properties of the magnetic core made into a finished winding will be attenuated to a certain extent, and when the winding wire diameter reaches φ1.5 or more, it is very easy for the magnetic core to break and cannot withstand the winding stress.
[0004] Therefore, the prior art still has the problem of being unable to effectively balance the volume and strength of the magnetic core. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high magnetic permeability nanocrystalline magnetic core and a preparation method thereof, aiming to solve the problem in the prior art that the core volume and the core strength cannot be effectively balanced, thereby effectively improving the core strength compared to the prior art when the core volume does not change significantly.
[0006] The first aspect of the present invention is to provide a method for preparing a high permeability nanocrystalline magnetic core, the preparation method comprising:
[0007] Winding the nanocrystalline ribbon to obtain a magnetic core roll;
[0008] Placing the magnetic core roll in an atmosphere furnace and performing heat treatment on the magnetic core roll to obtain a first magnetic core;
[0009] The first magnetic core is impregnated with silicate or epoxy resin, and the impregnated first magnetic core is baked in a tunnel furnace to solidify the first magnetic core to obtain a second magnetic core;
[0010] Mixing metal magnetic powder and organic resin according to a preset ratio to obtain a composite magnetic powder material;
[0011] The composite magnetic powder material is made into magnetic powder particles, and the magnetic powder particles are combined with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability.
[0012] According to one aspect of the above technical solution, the step of placing the magnetic core roll in an atmosphere furnace and heat treating the magnetic core roll to obtain a first magnetic core includes:
[0013] Placing the magnetic core roll in a vertical atmosphere furnace, evacuating the vertical atmosphere furnace, and introducing nitrogen into the vertical atmosphere furnace;
[0014] The magnetic core roll is heat treated, and a transverse magnetic field is applied to the magnetic core roll to obtain a first magnetic core.
[0015] According to one aspect of the above technical solution, the step of heat treating the magnetic core roll and applying a transverse magnetic field to the magnetic core roll to obtain a first magnetic core includes:
[0016] Heating the vertical atmosphere furnace at a first heating rate, applying a transverse magnetic field after the temperature reaches the first temperature and maintaining the temperature for a first time;
[0017] Continue heating at a second heating rate, and keep the temperature for a second time after the temperature reaches the second temperature;
[0018] Continue heating at a third heating rate, and keep the temperature for a third time after the temperature reaches a third temperature;
[0019] The magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset temperature drop rate to obtain a first magnetic core that is magnetically conductive.
[0020] According to one aspect of the above technical solution, the first temperature is 360°C-400°C, the second temperature is 440°C-480°C, and the third temperature is 530°C-570°C.
[0021] According to one aspect of the above technical solution, the vertical atmosphere furnace is heated at a first heating rate, and in the step of applying a transverse magnetic field and keeping the temperature for a first time after the temperature reaches the first temperature, a transverse magnetic field is applied to the magnetic core roll after the temperature reaches the first temperature, and the magnetic induction intensity of the transverse magnetic field is 1000±200Gs.
[0022] According to one aspect of the above technical solution, the magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset cooling rate to obtain a first magnetic core that is magnetically conductive, and a blower is used to blow-cool the magnetic core roll to room temperature.
[0023] According to one aspect of the above technical solution, the steps of preparing the composite magnetic powder material into magnetic powder particles, and combining the magnetic powder particles with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability include:
[0024] Using a mechanical granulator to make the composite magnetic powder material into magnetic powder particles;
[0025] pouring the magnetic powder particles into the lower hopper of an injection molding machine;
[0026] The second magnetic core is placed in a preset mold of the injection molding machine, and the magnetic powder particles are fed into the mold cavity under control so that the magnetic powder particles are bonded to the surface of the second magnetic core to obtain a nanocrystalline magnetic core with high magnetic permeability.
[0027] According to one aspect of the above technical solution, the mixing ratio of the metal magnetic powder to the organic resin in the composite magnetic material is 7:3-8:2, and the magnetic powder particles are 60-80 mesh particles.
[0028] According to one aspect of the above technical solution, the thickness of the magnetic powder particles bonded to the surface of the second magnetic core is 0.4 mm-0.6 mm.
[0029] The second aspect of the present invention is to provide a high permeability nanocrystalline magnetic core, which is prepared by the preparation method described in the above technical solution.
[0030] Compared with the prior art, the high permeability nanocrystalline magnetic core and the preparation method thereof shown in the present invention have the following beneficial effects:
[0031] The present invention obtains a magnetic core roll by pre-winding a magnetic core strip, then heat-treating the magnetic core roll to obtain a first magnetic core, then impregnating and baking the first magnetic core to fix the shape, to obtain a second magnetic core, and finally manufacturing magnetic powder particles containing metal magnetic powder and organic resin, and using injection molding to wrap the magnetic powder particles on the surface of the magnetic core, thereby obtaining a nanocrystalline magnetic core. The present invention utilizes the high strength and high stability characteristics of the composite powder as well as its own certain magnetic properties and insulation to compensate for the defects of direct spraying of the magnetic core or protection by a plastic shell. At the same time, the volume of the nanocrystalline magnetic core manufactured by the present invention can also be smaller than that of a shelled product of the same model, which can save installation space for back-end applications and significantly improve performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0033] Figure 1 The figure is a schematic diagram of a process for preparing a high-fluidity magnetic composite material in one embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. Several embodiments of the present invention are shown in the accompanying drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0036] The first aspect of the present invention is to provide a method for preparing a high permeability nanocrystalline magnetic core, the preparation method comprising:
[0037] Winding the nanocrystalline ribbon to obtain a magnetic core roll;
[0038] Placing the magnetic core roll in an atmosphere furnace and performing heat treatment on the magnetic core roll to obtain a first magnetic core;
[0039] The first magnetic core is impregnated with silicate or epoxy resin, and the impregnated first magnetic core is baked in a tunnel furnace to solidify the first magnetic core to obtain a second magnetic core;
[0040] Mixing metal magnetic powder and organic resin according to a preset ratio to obtain a composite magnetic powder material;
[0041] The composite magnetic powder material is made into magnetic powder particles, and the magnetic powder particles are combined with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability.
[0042] Further, the step of placing the magnetic core roll in an atmosphere furnace and heat treating the magnetic core roll to obtain a first magnetic core includes:
[0043] Placing the magnetic core roll in a vertical atmosphere furnace, evacuating the vertical atmosphere furnace, and introducing nitrogen into the vertical atmosphere furnace;
[0044] The magnetic core roll is heat treated, and a transverse magnetic field is applied to the magnetic core roll to obtain a first magnetic core.
[0045] Further, the step of heat treating the magnetic core roll and applying a transverse magnetic field to the magnetic core roll to obtain a first magnetic core includes:
[0046] Heating the vertical atmosphere furnace at a first heating rate, applying a transverse magnetic field after the temperature reaches the first temperature and maintaining the temperature for a first time;
[0047] Continue heating at a second heating rate, and keep the temperature for a second time after the temperature reaches the second temperature;
[0048] Continue heating at a third heating rate, and keep the temperature for a third time after the temperature reaches a third temperature;
[0049] The magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset temperature drop rate to obtain a first magnetic core that is magnetically conductive.
[0050] Further, the first temperature is 360°C-400°C, the second temperature is 440°C-480°C, and the third temperature is 530°C-570°C.
[0051] Further, the vertical atmosphere furnace is heated at a first heating rate, and in the step of applying a transverse magnetic field and keeping the temperature for a first time after the temperature reaches the first temperature, a transverse magnetic field is applied to the magnetic core roll after the temperature reaches the first temperature, and the magnetic induction intensity of the transverse magnetic field is 1000±200Gs.
[0052] Furthermore, the magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset cooling rate to obtain a first magnetic core that is magnetically conductive, and a blower is used to cool the magnetic core roll to room temperature.
[0053] Furthermore, the step of preparing the composite magnetic powder material into magnetic powder particles, and combining the magnetic powder particles with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability includes:
[0054] Using a mechanical granulator to make the composite magnetic powder material into magnetic powder particles;
[0055] pouring the magnetic powder particles into the lower hopper of an injection molding machine;
[0056] The second magnetic core is placed in a preset mold of the injection molding machine, and the magnetic powder particles are fed into the mold cavity under control so that the magnetic powder particles are bonded to the surface of the second magnetic core to obtain a nanocrystalline magnetic core with high magnetic permeability.
[0057] Furthermore, the mixing ratio of the metal magnetic powder to the organic resin in the composite magnetic material is 7:3-8:2, and the magnetic powder particles are 60-80 mesh particles.
[0058] Furthermore, the thickness of the magnetic powder particles bonded to the surface of the second magnetic core is 0.4 mm-0.6 mm.
[0059] The second aspect of the present invention is to provide a high permeability nanocrystalline magnetic core, which is prepared by the preparation method described in the above technical solution.
[0060] Compared with the prior art, the high permeability nanocrystalline magnetic core and the preparation method thereof shown in the present invention have the following beneficial effects:
[0061] The present invention obtains a magnetic core roll by pre-winding a magnetic core strip, then heat-treating the magnetic core roll to obtain a first magnetic core, then impregnating and baking the first magnetic core to fix the shape, to obtain a second magnetic core, and finally manufacturing magnetic powder particles containing metal magnetic powder and organic resin, and using injection molding to wrap the magnetic powder particles on the surface of the magnetic core, thereby obtaining a nanocrystalline magnetic core. The present invention utilizes the high strength and high stability characteristics of the composite powder as well as its own certain magnetic properties and insulation to compensate for the defects of direct spraying of the magnetic core or protection by a plastic shell. At the same time, the volume of the nanocrystalline magnetic core manufactured by the present invention can also be smaller than that of a shelled product of the same model, which can save installation space for back-end applications and significantly improve performance.
[0062] Embodiment 1
[0063] See also Figure 1 The first embodiment of the present invention provides a method for preparing a high permeability nanocrystalline magnetic core. The preparation method shown in this embodiment includes steps S10 to S50:
[0064] Step S10, winding the nanocrystalline ribbon to obtain a magnetic core roll.
[0065] In the present embodiment, the nanocrystalline ribbon is a nanocrystalline magnetic core ribbon with a thickness of 20-22 μm. The magnetic core roll is obtained by rolling. The magnetic core size of the magnetic core roll is uniformly OD*ID*HT=30*20*10 mm.
[0066] Specifically, during the rolling process of the nanocrystalline ribbon, a semi-automatic winding machine is used to wind the magnetic core, and the winding tightness of the magnetic core is controlled so that the magnetic core can naturally rebound into a round shape after being lightly pinched and released.
[0067] Step S20: placing the magnetic core roll in an atmosphere furnace and performing heat treatment on the magnetic core roll to obtain a first magnetic core.
[0068] In this embodiment, the step of heat treating the magnetic core roll and applying a transverse magnetic field to the magnetic core roll to obtain a first magnetic core includes:
[0069] Heating the vertical atmosphere furnace at a first heating rate, applying a transverse magnetic field after the temperature reaches the first temperature and maintaining the temperature for a first time;
[0070] Continue heating at a second heating rate, and keep the temperature for a second time after the temperature reaches the second temperature;
[0071] Continue heating at a third heating rate, and keep the temperature for a third time after the temperature reaches a third temperature;
[0072] The magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset temperature drop rate to obtain a first magnetic core that is magnetically conductive.
[0073] Further, the first temperature is 380°C, the second temperature is 460°C, and the third temperature is 550°C.
[0074] Further, the vertical atmosphere furnace is heated at a first heating rate, and in the step of applying a transverse magnetic field and keeping the temperature for a first time after the temperature reaches the first temperature, a transverse magnetic field is applied to the magnetic core roll after the temperature reaches the first temperature, and the magnetic induction intensity of the transverse magnetic field is 1000±200Gs.
[0075] Furthermore, the magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset cooling rate to obtain a first magnetic core that is magnetically conductive, and a blower is used to cool the magnetic core roll to room temperature.
[0076] Specifically, in this embodiment, after the magnetic core roll is placed in the atmosphere furnace, it will be vacuumed first, and then nitrogen will be introduced for protection. The heating power of the atmosphere furnace will be set, and the temperature will be increased according to the first heating rate to make the furnace temperature reach 380°C, and then kept warm for 30 minutes. Then, the temperature will be increased according to the second heating rate to make the furnace temperature reach 460°C and kept warm for 40 minutes. The temperature will be increased according to the third heating rate to make the furnace temperature reach 550°C. After keeping warm for 30 minutes, a blower will be used to quickly cool the magnetic core roll, and the cold will be maintained during the cooling process to maintain a constant magnetic field, thereby obtaining a first magnetic core that is magnetically conductive.
[0077] Among them, when the temperature is increased according to the first heating rate, the heating time from room temperature to 380°C is 30 minutes. If the room temperature is 30°C, the first heating rate is about 11.6°C / min. When the temperature is increased according to the second heating rate, the heating time from 380°C to 460°C is 40 minutes, and the second heating rate is 2°C / min. When the temperature is increased according to the third heating rate, the heating time from 460°C to 550°C is 60 minutes, and the third heating rate is 1.5°C / min.
[0078] It can be seen that in this embodiment, a three-stage heating process is used to heat treat the magnetic core roll. As the temperature increases, the heating rate becomes slower and the insulation time becomes longer.
[0079] Step S30, impregnating the first magnetic core with silicate or epoxy resin, and baking the impregnated first magnetic core in a tunnel furnace to solidify the first magnetic core to obtain a second magnetic core.
[0080] In this embodiment, the first magnetic core is impregnated with silicate. After heat treatment, the first magnetic core is impregnated with silicate and then baked in a tunnel furnace to solidify the first magnetic core and reduce the influence of external stress on the first magnetic core.
[0081] Step S40, mixing the metal magnetic powder and the organic resin according to a preset ratio to obtain a composite magnetic powder material.
[0082] In this embodiment, the mixing ratio of metal magnetic powder to organic resin is 7:3, and the composite magnetic powder material is obtained by fully mixing 70% of metal magnetic powder and 30% of organic resin.
[0083] Step S50, making the composite magnetic powder material into magnetic powder particles, and combining the magnetic powder particles with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability.
[0084] In this embodiment, the steps of preparing the composite magnetic powder material into magnetic powder particles, and combining the magnetic powder particles with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability include:
[0085] Using a mechanical granulator to make the composite magnetic powder material into magnetic powder particles;
[0086] pouring the magnetic powder particles into the lower hopper of an injection molding machine;
[0087] The second magnetic core is placed in a preset mold of the injection molding machine, and the magnetic powder particles are fed into the mold cavity under control so that the magnetic powder particles are bonded to the surface of the second magnetic core to obtain a nanocrystalline magnetic core with high magnetic permeability.
[0088] Specifically, after the metal magnetic powder and the organic resin are mixed in a ratio of 7:3 and stirred evenly, a mechanical granulator is used to prepare the composite magnetic powder material into small particles passing through a 65-mesh sieve to obtain magnetic powder particles. The magnetic powder particles are then poured into an injection molding machine, and the corresponding second magnetic core is embedded in the mold in advance. After the temperature is suitable, injection molding is performed, and the pressure is maintained for a period of time to be cured and formed, which is equivalent to wrapping the second magnetic core with magnetic powder particles. The nanocrystalline magnetic core can be taken out by opening the mold, which is specifically a magnetic ring structure. In this embodiment, magnetic powder particles with different performances can be obtained by mixing in different proportions, thereby adjusting the magnetism and strength of the product. At the same time, the wall thickness of the nanocrystalline magnetic core can be adjusted by the design of the mold.
[0089] In some preferred embodiments, the magnetic powder particles are small particles that pass through a 65-mesh sieve, and the thickness of the magnetic powder particles bonded to the surface of the second magnetic core is 0.5 mm by injection molding through an injection molding machine. Optionally, the mesh size of the magnetic powder particles can also be 60-80 meshes, and the thickness of the magnetic powder particles wrapping the second magnetic core can also be 0.5 mm-0.6 mm.
[0090] The size of the nanocrystalline magnetic core prepared in this embodiment is compared with the directly sprayed magnetic core and the shelled magnetic core in the prior art. The size comparison results are shown in Table 1:
[0091] Table 1
[0092]
[0093] It can be seen from Table 1 that, using a magnetic core roll of the same size, the nanocrystalline magnetic core shown in this embodiment can reduce the size of the directly sprayed magnetic core and the shelled magnetic core in the prior art by about 27.4% in volume.
[0094] The compressive strength of the nanocrystalline magnetic core prepared in this embodiment is compared with that of the directly sprayed magnetic core and the shelled magnetic core in the prior art. The compressive strength comparison results are shown in Table 2:
[0095] Table 2
[0096]
[0097] According to Table 2, the nanocrystalline magnetic core shown in this embodiment has a similar ability to resist external pressure as the shelled magnetic core, and is significantly better than the directly sprayed magnetic core, which indicates that the nanocrystalline magnetic core prepared by the method shown in this embodiment has a strong ability to resist external pressure.
[0098] After winding 20TS with φ1.5 copper wire, the nanocrystalline magnetic core prepared in this embodiment is compared with the directly sprayed magnetic core and the shelled magnetic core in the prior art for winding performance attenuation. The winding performance attenuation comparison results are shown in Table 3:
[0099] Table 3
[0100]
[0101] According to Table 3, the performance of the nanocrystalline magnetic core shown in this embodiment is basically not attenuated after winding, which is basically similar to the shelled magnetic core, and is significantly better than the directly sprayed magnetic core.
[0102] Among them, the negative numbers in Table 3 represent an increase, that is, the performance is better after winding. The winding wire diameter and number of turns of the three cores are consistent.
[0103] The inductance (magnetic permeability) of the nanocrystalline magnetic core prepared in this embodiment is compared with the directly sprayed magnetic core and the shelled magnetic core in the prior art. The comparison results are shown in Table 4:
[0104] Table 4
[0105]
[0106] According to Table 4, when the nanocrystalline magnetic core shown in this embodiment is used, since the metal magnetic powder in the magnetic powder particles formed on the surface of the second magnetic core by injection molding has certain magnetic properties, after it is combined with the second magnetic core to form a nanocrystalline magnetic core, compared with the shelled magnetic core in the prior art, the inductance (magnetic permeability) is increased by 6%-10%, and compared with the directly sprayed magnetic core, the inductance (magnetic permeability) is increased by more than 30%.
[0107] Therefore, compared with the prior art, the nanocrystalline magnetic core is prepared by the preparation method shown in this embodiment, which has the following beneficial effects:
[0108] Embodiment 2
[0109] The second embodiment of the present invention also provides a method for preparing a high permeability nanocrystalline magnetic core. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment, except that:
[0110] In this embodiment, the mixing ratio of metal magnetic powder to organic resin is 8:2, and the composite magnetic powder material is obtained by fully mixing 80% of metal magnetic powder with 20% of organic resin. The nanocrystalline magnetic core is manufactured based on the same process.
[0111] The nanocrystalline magnetic core shown in this embodiment is tested and compared with the directly sprayed magnetic core and the shelled magnetic core in the prior art. The comparison results are shown in Table 5:
[0112] Table 5
[0113]
[0114] According to Table 5, in this embodiment, by adjusting the ratio of metal magnetic powder to organic resin in the composite magnetic powder material, and then using an injection molding machine to wrap the second magnetic core, a nanocrystalline magnetic core is obtained, and the magnetic permeability advantage is still very obvious, and the magnetic core strength is large, and the winding attenuation is minimal year-on-year.
[0115] Embodiment 3
[0116] The third embodiment of the present invention also provides a method for preparing a high permeability nanocrystalline magnetic core. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment, except that:
[0117] In this embodiment, after the metal magnetic powder and the organic resin are mixed in a ratio of 8:2 and stirred evenly, a composite magnetic powder material is obtained, and a mechanical granulator is used to prepare the composite magnetic powder material into small particles passing through a 75-mesh sieve to obtain magnetic powder particles.
[0118] The nanocrystalline magnetic core shown in this embodiment is tested and compared with the directly sprayed magnetic core and the shelled magnetic core in the prior art. The comparison results are shown in Table 6:
[0119] Table 6
[0120]
[0121]
[0122] According to Table 6, in this embodiment, by adjusting the mesh size of the magnetic powder particles made of the composite magnetic powder material and then using an injection molding machine to wrap the second magnetic core, the magnetic permeability advantage is still very obvious, the magnetic core strength is large, and the winding attenuation is minimal year-on-year.
[0123] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0124] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a high permeability nanocrystalline magnetic core, characterized in that: The preparation method comprises: Winding the nanocrystalline ribbon to obtain a magnetic core roll; Placing the magnetic core roll in an atmosphere furnace and performing heat treatment on the magnetic core roll to obtain a first magnetic core; The first magnetic core is impregnated with silicate or epoxy resin, and the impregnated first magnetic core is baked in a tunnel furnace to solidify the first magnetic core to obtain a second magnetic core; Mixing metal magnetic powder and organic resin according to a preset ratio to obtain a composite magnetic powder material; The composite magnetic powder material is made into magnetic powder particles, and the magnetic powder particles are combined with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability.
2. The method for preparing a high permeability nanocrystalline magnetic core according to claim 1, characterized in that: The step of placing the magnetic core roll in an atmosphere furnace and heat treating the magnetic core roll to obtain a first magnetic core includes: Placing the magnetic core roll in a vertical atmosphere furnace, evacuating the vertical atmosphere furnace, and introducing nitrogen into the vertical atmosphere furnace; The magnetic core roll is heat treated, and a transverse magnetic field is applied to the magnetic core roll to obtain a first magnetic core.
3. The method for preparing a high permeability nanocrystalline magnetic core according to claim 2, characterized in that: The step of heat treating the magnetic core roll and applying a transverse magnetic field to the magnetic core roll to obtain a first magnetic core comprises: Heating the vertical atmosphere furnace at a first heating rate, applying a transverse magnetic field after the temperature reaches the first temperature and maintaining the temperature for a first time; Continue heating at a second heating rate, and keep the temperature for a second time after the temperature reaches the second temperature; Continue heating at a third heating rate, and keep the temperature for a third time after the temperature reaches a third temperature; The magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset temperature drop rate to obtain a first magnetic core that is magnetically conductive.
4. The method for preparing a high permeability nanocrystalline magnetic core according to claim 3, characterized in that: The first temperature is 360°C-400°C, the second temperature is 440°C-480°C, and the third temperature is 530°C-570°C.
5. The method for preparing a high permeability nanocrystalline magnetic core according to claim 3, characterized in that: The vertical atmosphere furnace is heated at a first heating rate, and in the step of applying a transverse magnetic field and keeping the temperature for a first time after the temperature reaches the first temperature, a transverse magnetic field is applied to the magnetic core roll after the temperature reaches the first temperature, and the magnetic induction intensity of the transverse magnetic field is 1000±200Gs.
6. The method for preparing a high permeability nanocrystalline magnetic core according to claim 3, characterized in that: The magnetic core roll in the vertical atmosphere furnace is taken out, and the magnetic core roll is cooled according to a preset temperature drop rate to obtain a first magnetic core that is magnetically conductive, and a blower is used to cool the magnetic core roll to room temperature.
7. The method for preparing a high permeability nanocrystalline magnetic core according to any one of claims 1 to 6, characterized in that: The steps of preparing the composite magnetic powder material into magnetic powder particles, and combining the magnetic powder particles with the second magnetic core by injection molding to obtain a nanocrystalline magnetic core with high magnetic permeability include: Using a mechanical granulator to make the composite magnetic powder material into magnetic powder particles; pouring the magnetic powder particles into the lower hopper of an injection molding machine; The second magnetic core is placed in a preset mold of the injection molding machine, and the magnetic powder particles are fed into the mold cavity under control so that the magnetic powder particles are bonded to the surface of the second magnetic core to obtain a nanocrystalline magnetic core with high magnetic permeability.
8. The method for preparing a high permeability nanocrystalline magnetic core according to claim 7, characterized in that: The mixing ratio of the metal magnetic powder to the organic resin in the composite magnetic material is 7:3-8:2, and the magnetic powder particles are 60-80 mesh particles.
9. The method for preparing a high permeability nanocrystalline magnetic core according to claim 7, characterized in that: The thickness of the magnetic powder particles bonded to the surface of the second magnetic core is 0.4 mm to 0.6 mm.
10. A high permeability nanocrystalline magnetic core, characterized in that: The high permeability nanocrystalline magnetic core is prepared by the preparation method described in any one of claims 1-9.
Citation Information
Patent Citations
Inductor and manufacturing method thereof
CN101692385A
Preparation process of amorphous alloy iron core cake for iron core reactor
CN112466642A
Preparation method of amorphous or nanocrystalline anti-surge magnetic core
CN118522549A
Surface packaging technique method for non-crystalline metal magnetic core
CN1805085A
Composite magnetic material, dust core using the same and magnetic element
JP2007134591A